Using the Satisfaction with Life Scale in People with Parkinson’s Disease: A Validation Study in Different European Countries - Ramona Lucas-Carrasco; Brenda L. Den Oudsten; Erhan Eser; Michael J. Power (The Scientific World Journal)
Background. Overall, people with chronic illnesses have lower life satisfaction compared to nonclinical populations. The objective of this international study was to examine the psychometric properties of the Satisfaction with Life Scale (SWLS) in patients with Parkinson’s disease (PD). Methods. PD patients (n=350) were recruited and interviewed at different specialized services in the United Kingdom, Spain, Czech Republic, Italy, and The Netherlands. A questionnaire set including a measure of life satisfaction, quality of life (QoL), self-reported health and disability status, and sociodemographic information was used. Acceptability, reliability, and validity were examined. Results. The internal consistency was good (α = 0.81). The scale structure was satisfactory (comparative fit index = 0.99; root mean square error of approximation = 0.08). The SWLS was able to discriminate between healthy and unhealthy, disabled and nondisabled, and those perceiving a more severe impact of the disability on their lives. Concurrent validity using multiple linear regression models confirmed associations between SWLS and QoL and age. Conclusions. This study is the first to report on the use of the SWLS in PD patients in different European countries. It is a useful tool in assessing satisfaction with life in PD patients through the continuum of care.